Axial compressive behavior of square concrete columns reinforced with innovative closed-type winding GFRP stirrups. (15th May 2018) - Dong, Heng-Lei; Wang, Daiyu; Wang, Zhenyu; Sun, Yunlong
Abstract: Conventional fiber-reinforced polymer (FRP) rod stirrups are characterized by at least one side overlap, where premature bond slip failure is likely to occur, resulting in low confinement efficiency. To overcome this shortcoming, an innovative closed-type winding glass FRP (CW-GFRP) stirrup was proposed by winding continuous filaments on the mould. This paper also presented an experimental study on the axial compressive behavior of 16 large-scale columns (300 × 300 × 900 mm), which were reinforced longitudinally with identical steel bars and transversely with different stirrups, namely steel, CW-GFRP or conventional GFRP rod stirrups. The confinement efficiency of these stirrups was compared regarding the failure modes, axial load capacity and ultimate axial strain. Test results indicated that columns reinforced with conventional GFRP rod stirrups exhibited bond slip failure after spalling of concrete cover, while CW-GFRP confined columns avoided this failure. The proposed CW-GFRP stirrups performed best in improving the ductility of columns. When stirrup spacing was 75 mm, an increase of 95% and 180% in ultimate axial strain was achieved for CW-GFRP confined columns compared with their steel and GFRP rod stirrup counterparts. Columns with CW-GFRP stirrups spaced at 50 mm exhibited monotonically ascending load–strain responses and achieved the ultimate strain up to 5.51%.